1993
DOI: 10.1105/tpc.5.11.1575
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of MPG1, a gene involved in pathogenicity from the rice blast fungus Magnaporthe grisea.

Abstract: Differential cDNA cloning was used to identify genes expressed during infectious growth of the fungal pathogen Magnaporthe grisea in its host, the rice plant. We characterized one of these genes, MPG1, in detail. Using a nove1 assay to determine the proportion of fungal biomass present in the plant, we determined that the MPGl transcript was 60-fold more abundant during growth in the plant than in culture. Mpgl mutants have a reduced ability to cause disease symptoms that appears to result from an impaired abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
618
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 750 publications
(635 citation statements)
references
References 44 publications
8
618
1
Order By: Relevance
“…Some of these genes, like CgDN3 (Colletotrichum gloeosporioides), AVR9 (Cladosporium fulvum) and MPG1 (Magnaporthe grisea) are also upregulated during conditions of nitrogen starvation (Stephenson et al, 2000;Talbot et al, 1993;Van den Ackerveken et al, 1994). For Avr9 and Mpg1 it was shown that expression (partly) depends on a general nitrogen response factors (NRF1 and NPR1, respectively) (Lau and Hamer, 1996;Perez-Garcia et al, 2001;Soanes et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these genes, like CgDN3 (Colletotrichum gloeosporioides), AVR9 (Cladosporium fulvum) and MPG1 (Magnaporthe grisea) are also upregulated during conditions of nitrogen starvation (Stephenson et al, 2000;Talbot et al, 1993;Van den Ackerveken et al, 1994). For Avr9 and Mpg1 it was shown that expression (partly) depends on a general nitrogen response factors (NRF1 and NPR1, respectively) (Lau and Hamer, 1996;Perez-Garcia et al, 2001;Soanes et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The primer pairs Qip-Up-2F/2R and Qip-Down-2F/2R were used to amplify two 0.9-kb fragments, which were used to test for homologous recombination. Wild-type A8 strain protoplasts were prepared as described previously (Talbot et al 1993). Protoplasts were transformed with the knockout plasmid pKO-Qip using a PEG-CaCl 2 -mediated procedure (Nakayashiki et al 1999).…”
Section: Methodsmentioning
confidence: 99%
“…grisea strain Guy11 was used as wild type and cultured in complete medium (CM) as described previously (Talbot et al, 1993). Escherichia coli strain DH5α was used as a host for plasmid amplification.…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…Protoplasts isolation was carried out as described by Talbot et al(1993) with minor modifications. Briefly, a 3-cm 2 square of Guy11 mycelia was cut from the surface of the CM agar plate, incubated in 300 ml liquid CM medium at 28 °C on a rotary shaker at 125 r/min for 48 h. The mycelia were harvested by filtration and protoplasts were produced by Glucanex (Denmark) digestion in 0.7 mol/L NaCl.…”
Section: Transformation Of M Griseamentioning
confidence: 99%
See 1 more Smart Citation